El priorato de Santa Cilia de Panzano (Huesca) en el siglo XII: The Priory of Santa Cilia de Panzano (Huesca, Spain) in the 12th Century - Viruete Erdozáin, Roberto (Aragón en la Edad Media, 2020)
Abstract: This paper focuses on the history of priory of Santa Cilia de Panzano de Huesca in the 12th Century. The possessions of this priory were in the valleys of the rivers Calcón and Formiga in a muslim Labata castle area, a porcion of the ancient muslim area of Huesca. The French abbey Saint-Pons-de-Thomières founded the priory of the Santa Cilia de Panzano between 1099 and 1101. Her possessions mainly formed by donation of the king Sancho Ramirez and by native nobility. The economical exploitation of Santa Cilia de Panzano’s priory is a main question of the paper. Thus, I analyse the terms of land use, and the conflicts between the priory and the peasants, and the feudal incomes. Key words: Santa Cilia de Panzano, feudal incomes, priory, dominion exploitation, Hoya de Huesca, 12th Century. Resumen: El artículo se centra en la historia del priorato de Santa Cilia de Panzano de Huesca en el siglo xii. El patrimonio del priorato de Santa Cilia de Panzano estuvo localizado en las cuencas hidrográficas de los ríos Calcón y Formiga, en la zona controlada por el castillo musulmán de Labata, dentro del distrito musulmán de Huesca. El monasterio francés de Saint-Pons-de-Thomières fundó el priorato de Santa Cilia de Panzano entre 1099 y 1101. Las donaciones de Sancho Ramírez y de la nobleza oriunda de la zona fueron la base de sus posesiones. La explotación del dominio de Santa Cilia de Panzano es objeto de esta investigación que analiza las condiciones del uso de la tierra, los conflictos señoriales y las rentas feudales. Palabras clave: Santa Cilia de Panzano, rentas feudales, priorato, explotación del dominio, Hoya de Huesca, siglo xii.